2012
DOI: 10.1186/1756-8722-5-1
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of arsenic trioxide metabolites in peripheral blood and bone marrow from an acute promyelocytic leukemia patient

Abstract: BackgroundSpeciation of arsenic trioxide (ATO) metabolites in clinical samples such as peripheral blood (PB) from acute promyelocytic leukemia (APL) patients has been conducted. However, speciation of arsenicals in bone marrow (BM) has not yet been performed. Profiles of arsenic speciation in plasma of BM were thus investigated and compared with those of PB plasma from a relapsed APL patient. The total arsenic concentrations in high molecular weight fraction (HMW-F) of BM and PB plasma were also determined.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
59
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 36 publications
3
59
0
Order By: Relevance
“…It is noteworthy that CD34 expression, well-known to be present in hematopoietic progenitor cells and absent in NB4 cells (8,18), significantly decreased after treatment with ATRA in HT93A cells. These results suggest that CD34, CD11b and CD15 could be used as a parameter to evaluate the level of differentiation in clinical therapy as shown in our previous clinical observation (25). There are only a few APL cell lines and most in vitro experiments are performed with NB4 cells.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…It is noteworthy that CD34 expression, well-known to be present in hematopoietic progenitor cells and absent in NB4 cells (8,18), significantly decreased after treatment with ATRA in HT93A cells. These results suggest that CD34, CD11b and CD15 could be used as a parameter to evaluate the level of differentiation in clinical therapy as shown in our previous clinical observation (25). There are only a few APL cell lines and most in vitro experiments are performed with NB4 cells.…”
Section: Discussionsupporting
confidence: 60%
“…Lower concentration of ATO induced differentiation of HT93A cells. On the basis of our previous study, in which the blood level of ATO in APL patients was investigated (24,25), plasma concentration of ATO in either bone marrow or peripheral blood kept the effective level of differentiation induction for HT93A cells. Next, we demonstrated that both ATRA and ATO induced differentiation in HT93A cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we have demonstrated for the first time that these arsenic metabolites also existed in cerebrospinal fluid [67], in which the concentrations of arsenic reached levels necessary for differentiation induction [68,69]. We further investigated for the first time the arsenic speciation in plasma of bone marrow (BM), and demonstrated that speciation profiles of BM plasma were very similar to those of PB plasma, suggesting that speciation analysis of PB plasma could be predicative for BM speciation [70]. These findings on the pharmacokinetics of ATO in APL patients provide a new insight into clinical applications of ATO, and may contribute to better therapeutic protocols [4].…”
Section: Potential Future Application Of Polyphenolic Compounds Alonmentioning
confidence: 99%
“…This lack of progress in the treatment of malignant melanoma is caused in part by the high invasiveness of melanomas, thus making surgical treatment lowly effective. Conventional chemotherapy of this cancer is also inefficient [4]. Median survival of patients with non-cutaneous metastasis is less than one year, with a 5-year survival not more than 10% even in developed countries [5].…”
mentioning
confidence: 99%
“…Median survival of patients with non-cutaneous metastasis is less than one year, with a 5-year survival not more than 10% even in developed countries [5]. Thus, the search for specific markers of this disease, especially specific surface markers [6] and altered signaling pathways, for development of immunotherapy and different types of targeted therapy [4, 7] is of great interest.…”
mentioning
confidence: 99%